1989
DOI: 10.1007/bf02222239
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effects of cimetidine and ranitidine in histamine provocation tests in atopic asthma

Abstract: The effects of cimetidine and ranitidine on the bronchial reactivity in the group of 10 patients with atopic bronchial asthma are presented. The patients received 800 mg of cimetidine daily for 6 days and, after a three-day interval, 300 mg of ranitidine daily for a further 6 days. Bronchial reactivity to histamine was determined before the administration of each drug and on the third and sixth days of each course of treatment. A comparison of the effect of cimetidine and ranitidine on the bronchial reactivity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1991
1991
2016
2016

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Initially, there were concerns that these medications may cause clinical worsening of asthma because of H2 receptor blockade in the bronchial tree (70)(71)(72). Although some investigators reported that H2 receptor blockers increase bronchial reactivity, their use in asthma appears to be safe (73)(74)(75). A recent critical review identified 12 English-language studies of the effects of medical antireflux therapy in people with asthma with GER (76).…”
Section: Effects Of Medical Antirefluxmentioning
confidence: 99%
“…Initially, there were concerns that these medications may cause clinical worsening of asthma because of H2 receptor blockade in the bronchial tree (70)(71)(72). Although some investigators reported that H2 receptor blockers increase bronchial reactivity, their use in asthma appears to be safe (73)(74)(75). A recent critical review identified 12 English-language studies of the effects of medical antireflux therapy in people with asthma with GER (76).…”
Section: Effects Of Medical Antirefluxmentioning
confidence: 99%